IMPLEMENTASI PENYALURAN DANA ALOKASI KHUSUS FISIK BIDANG KESEHATAN DALAM MENDUKUNG PEMULIHAN KESEHATAN - Ramdan, Irvanjaya; Malik, Syahrizal Suwardana; Purnama, Dera Toni (Ensiklopedia of Journal, 2022)
The purpose of this study was to determine the implementation, obstacles and efforts made by the Subang District Health Office in the distribution of the physical Special Allocation Fund (DAK) in the healthsector in supporting post-covid-19 health recovery. The theory used by the author is Edward III's theory by analyzing the dimensions of Information Delivery, Resources, Disposition, and Bureaucratic Structure. The research method used is descriptive qualitative research with an inductive approach. The data collection technique used in this research is the technique of Observation, Interview, and Documentation. The results showed that the implementation of Fund Distribution The Special Allocation for Physical Health (DAK) for Physical Health has been running in accordance with the applicable technical guidelines, but in its realization there are still problems such as problems in the development of Labkesda. Obstacles faced such as the lack of trust of the Subang Regency government towards the Subang Regency Health Office which caused the planning program to be delayed, all meetings using the virtual method due to the unfinished Covid-19 condition causing uncertainty, there were still errors in the preparation of letters related to the implementation of the Physical DAK. Health, and the condition of goods that have run out while being procured.